The 1966 Financial Crisis: A Case of Minskian Instability? - L. Randall Wray (Levy Economics Institute of Bard College, 1999)
The so-called credit crunch of 1966 has long been recognized as the first significant postwar financial crisis and one that required the first important intervention by the Federal Reserve Bank. In the midst of the robust postwar expansion, the Fed began to fear inflation and tightened monetary policy to the point at which profitability of financial institutions was threatened. As Minsky argued, "By the end of August, the disorganization in the municipals market, rumors about the solvency and liquidity of savings institutions, and the frantic position-making efforts by money-market banks generated what can be characterized as a controlled panic. The situation clearly called for Federal Reserve action." The Fed was forced to enter as a lender of last resort to save the muni bond market, which in effect validated practices that were stretching liquidity. As a result of Fed intervention, the economy continued to expand, new financial practices emerged and were validated, leverage ratios increased, memories of the Great Depression faded, and markets came to expect that big government and the Fed would come to the rescue as needed. That 1966 crisis was only a minor speed bump on the road to Minskian fragility. To some extent, 1966 proved to be the first verification of the "financial instability hypothesis" that Minsky had been developing since the late 1950s, and the events of that year would stimulate further development of his analysis of the early postwar transition from a "robust" financial system toward a "fragile" financial system.
Keywords: 330